2008
DOI: 10.2110/palo.2007.p07-056r
|View full text |Cite
|
Sign up to set email alerts
|

Isotope sclerochronology of Mercenaria mercenaria, M. Campechiensis, and their natural hybrid form: Does genotype matter?

Abstract: Isotopic variation in northern and southern hard clam (quahog)shells is used in studies including paleoecology, paleoclimatology, and archaeology. It is unknown, however, whether species-specific isotopic differences exist. Three genotypes-Mercenaria mercenaria, M. campechiensis, and their natural hybrid form-are found in coastal Florida waters and differentiation of genotypes can be difficult to determine morphologically. This issue may be problematic when using archaeological shells as paleoclimate archives,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Clark, 1979;Quitmyer et al, 1985Quitmyer et al, , 1997Jones et al, 1989, in press;Jones and Quitmyer, 1996;Jones et al, in press;Elliot et al, 2003;Surge and Walker, 2006;Walker and Surge, 2006;Andrus and Crowe, 2008;O'Brian and Thomas, 2008). Two quahog species (Mercenaria mercenaria and M. campeciensis) and a hybrid exist in this area, but a comparative analysis showed no discernible differences in oxygen isotope fractionation between their shells (Surge et al, 2008). Species identification, which is difficult using hard tissues alone, is therefore not necessary in this clam.…”
Section: Archaeological Contextmentioning
confidence: 87%
“…Clark, 1979;Quitmyer et al, 1985Quitmyer et al, , 1997Jones et al, 1989, in press;Jones and Quitmyer, 1996;Jones et al, in press;Elliot et al, 2003;Surge and Walker, 2006;Walker and Surge, 2006;Andrus and Crowe, 2008;O'Brian and Thomas, 2008). Two quahog species (Mercenaria mercenaria and M. campeciensis) and a hybrid exist in this area, but a comparative analysis showed no discernible differences in oxygen isotope fractionation between their shells (Surge et al, 2008). Species identification, which is difficult using hard tissues alone, is therefore not necessary in this clam.…”
Section: Archaeological Contextmentioning
confidence: 87%
“…For M. mercenaria populations on the Atlantic coast, estimates of the VBGF growth constant K normally range between 0.20/y and 0.35/y (Jones et al 1989, Harding 2007). In cooler areas-for example, Southampton water in the United Kingdom and in Snug Harbour, Cape Cod, MA-low growth constants been reported (0.149 (Brown et al 2010) and 0.117 (Surge et al 2008)), and these were in relatively shallow water.…”
Section: Discussionmentioning
confidence: 99%
“…The annual periodicity of increment formation in the shell of M. mercenaria has been demonstrated by mark-and-recapture experiments (Peterson et al 1983) stable isotope profiles (Jones et al 1990, Jones & Quitmyer 1996, Surge et al 2008, and sequential sampling (Clark 1979, Peterson et al 1985, Jones et al 1990, Arnold et al 1991, Arnold et al 1998. In this article, we report the new maximum age observed for this species as well as growth parameters of a population of M. mercenaria containing the longest lived members of the species.…”
Section: Introductionmentioning
confidence: 94%
“…Earlier studies reported that oxygen isotope ratios in M. mercenaria and M. campechiensis can be used to reconstruct ambient environmental conditions (Elliot et al, 2003; Surge and Walker, 2006; Surge et al, 2008). However, δ 18 O w of estuarine water is difficult to constrain, but here we use this to our advantage.…”
Section: Discussionmentioning
confidence: 99%